H.I.V.E. : escape velocity / 3 - Walden, Mark (H.I.V.E., 2011)
Otto, struggling to cope with abilities that are just starting to manifest themselves, is dismayed when Number One appoints a new headmistress to the Higher Institute of Villainous Education to replace the missing Dr. Nero, and decides it is imperative that he rescue Nero from the forces of H.O.P.E., but must first break into M16.